Neutron studies of Na-ion battery materials. (27th September 2021) - Shah, Ami R; Shutt, Rebecca R C; Smith, Keenan; Hack, Jennifer; Neville, Tobias P; Headen, Thomas F; Brett, Dan J L; Howard, Christopher A; Miller, Thomas S; Cullen, Patrick L
Abstract: The relative vast abundance and more equitable global distribution of terrestrial sodium makes sodium-ion batteries (NIBs) potentially cheaper and more sustainable alternatives to commercial lithium-ion batteries (LIBs). However, the practical capacities and cycle lives of NIBs at present do not match those of LIBs and have therefore hindered their progress to commercialisation. The present drawback of NIB technology stems largely from the electrode materials and their associated Na + ion storage mechanisms. Increased understanding of the electrochemical storage mechanisms and kinetics is therefore vital for the development of current and novel materials to realise the commercial NIB. In contrast to x-ray techniques, the non-dependency of neutron scattering on the atomic number of elements ( Z ) can substantially increase the scattering contrast of small elements such as sodium and carbon, making neutron techniques powerful for the investigation of NIB electrode materials. Moreover, neutrons are far more penetrating which enables more complex sample environments including in situ and operando studies. Here, we introduce the theory of, and review the use of, neutron diffraction and quasi-elastic neutron scattering, to investigate the structural and dynamic properties of electrode and electrolyte materials for NIBs. To improve our understanding of the actual sodium storage mechanisms and identify intermediate stages during charge/discharge, ex situ, in situ, and operando neutron experiments are required. However, to date there are few studies where operando experiments are conducted during electrochemical cycling. This highlights an opportunity for research to elucidate the operating mechanisms within NIB materials that are under much debate at present.